Structural dynamics of calmodulin-ryanodine receptor interactions: electron paramagnetic resonance using stereospecific spin labels - Cheng Her (Nature Portfolio, 2018)
Abstract We have used electron paramagnetic resonance, with rigid and stereospecific spin labels, to resolve structural states in calmodulin (CaM), as affected by binding of Ca and a CaM-binding peptide (RyRp) derived from the ryanodine receptor (RyR), the Ca channel that triggers muscle contraction. CaM mutants containing a pair of cysteines in the N-lobe and/or C-lobe were engineered and labeled with a stereospecifically bound bifunctional spin label (BSL). RyRp was synthesized with and without TOAC (a stereospecifically attached spin-labeled amino acid) substituted for a single amino acid near the N-terminus. Intramolecular DEER distance measurements of doubly-labeled BSL-CaM revealed that CaM exists in dynamic equilibrium among multiple states, consistent with open, closed, and compact structural models. Addition of RyRp shifted the equilibrium partially toward the compact state in the absence of Ca, and completely toward the compact state in the presence of Ca, supporting a conformational selection model. Inter-protein distance measurements show that Ca stabilizes the compact state primarily by inducing ordered binding of the CaM N-lobe to RyRp, while only slightly affecting the C-lobe. The results provide insight into the structural mechanism of CaM-mediated RyR regulation, while demonstrating the power of using two types of rigidly and stereospecifically bound spin labels.